High-speed rail transportation: key factors for the Australian eastern states. (14th April 2020) - Gharehbaghi, Koorosh; McManus, Kerry; Robson, Kathryn; Paterno, David; Myers, Matt
In Australia, where the population is contained mainly in series of widely dispersed centres and towns, separated by very long distances, the case for High-Speed Rail (HSR) has generally been less compelling. Subsequently, this research reviews and assesses the implications and advantages of building an HSR passenger-focused transport network in Australia - in particular for the eastern region, where the majority of the nation's population is concentrated. To support this synopsis, European and other HSR systems are reviewed as a capstone precedent for the purpose of lessons to be learned. Using empirical and factor analyses it was found that, the Australia HSR would subsequently increase the transportation sustainability and performance, via reduction in travelling time together with more regional zone coverage. Ultimately, such improvements would particularly benefit the Australian regional communities via appropriate transit of passengers.